Rechtsprobleme und wirtschaftliche Vertretbarkeit einer Kulturflatrate - Überarbeitung des im Auftrag der Bundestagsfraktion Bündnis 90 - Spindler, Gerald (Universitätsverlag Göttingen, 2014)
The Internet and the proceeding digitalisation of content - such as music, videos and written texts - have led to profound and complex challenges in the field of Copyright Law, especially with regard to questions of enforcement as well as adequate compensation of right holders. In recent years, several alternative compensation schemes have been proposed, seeking to solve these issues. In Germany, the discussion still focuses on the so-called "cultural flatrate", that is, in a nutshell, a limitation to copyrights which would legalize sharing of content online. Every holder of a broadband connection to the Internet would have to pay a monthly fee which would be used to remunerate the right holders. This advisory opinion was compiled on behalf of the parliamentary group of the German political party "Bündnis 90/DIE GRÜNEN". The author comprehensively analyses the feasibility of the described alternative compensation scheme under German and European law, discussing both legal and economic obstacles and possible impacts based on a variety of different economic prerequisites.